PRACTICAL STUDY OF THE PSYCHOLOGICAL CHARACTERISTICS OF ADOLESCENTS WITH DEVIANT BEHAVIOR - Kasimova Nodiraxon Inomovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides for the fact that today a teenager is required to increase the level of self-acceptance at the expense of personality traits, successful communication, universal qualities and appearance, in addition, the technology and system of managing deviant behavior in adolescents with difficult “I represent” correction is intended to provide psychological and pedagogical accompaniment to the success of educational subjects.